Quinoa (Chenopodium quinoa) reaction to herbicide residue in a Brazilian Savannah soil - Santos, Roberto Lorena de Barros; Spehar, Carlos Roberto; Vivaldi, Lucio (Pesquisa Agropecuaria Brasileira, 2003)
e quinoa (Chenopodium quinoa Willd.) cultivation, one of the most promising in double cropping with soybeans or maize, depends on weed control. The objective of this work was to evaluate quinoa reaction to herbicide residue in a savannah soil. Six herbicide treatments, trifluralin, pendimethalin, clomazone, imazaquin, trifluralin + imazaquin and control, were applied, prior to summer cultivation of soybean, in a Dark-Red Latosol (typic Haplustox). Soybean cultivar BR 9 Savana was grown and soil samples were collected at 15, 38, 100, 145 and 206 days after treatment and stored at -5oC. Bioassays were conducted in greenhouse, using quinoa, cultivar Q18. Imazaquin was the most harmful to quinoa seedlings, up to 206 days after application, followed by clomazone 15-38 days after application; trifluralin and pendimethalin had no residual effect. These results suggest that a broad-base screening should be conducted.